Research on Resource Allocation Effect of China's OFDI on Equipment Manufacturing Industry - Chen, Shaogui (International Journal of Emerging Trends in Social Sciences, 2021)
Based on the panel data and time series data of China's 30 provinces (excluding Tibet) from 2004 to 2017, this paper analyzes the impact of China's OFDI on the resource allocation effect of equipment manufacturing industry through regression model. The empirical results show that China's OFDI has a significant positive effect on the resource allocation effect of equipment manufacturing industry, and with every unit of China's OFDI increasing, the profit margin of main business (PMB) of the equipment manufacturing industry will increase 0.087 percentage points. From the regional point of view, the growth of OFDI in Northeast China has a significant positive impact on the PMB of the equipment manufacturing industry, and its positive impact is the largest, followed by the eastern region, and the central and western regions have a significant negative impact. From the perspective of OFDI gradient, China's forward OFDI to developing countries and reverse OFDI to developed countries have a significant positive impact on the PMB of equipment manufacturing industry, and the impact of forward OFDI is more significant. Finally, this paper puts forward some suggestions on how to improve the efficiency of China's equipment manufacturing industry.